The Role of Nurses in Enhancing Medication Adherence and Patient Outcomes in Hypertension Management - Ulla, Ully Widya Rochmatil; Kurniasari, Heny; Pasaribu, Elsa; Sitohang, Lesly Grenia (Institute of Accounting Research and Novation (IARN), 2025)
Acute respiratory tract infection (ARI) is a disease that is often found and is transmitted from the upper or lower respiratory tract which can cause a spectrum of diseases ranging from mild infections to severe and fatal diseases, depending on the causative pathogen and environmental factors. This study aims to determine the description of drug use in patients with Acute Respiratory Tract Infections (ARI) based on the Patient Visit Book at the UPT. Narumonda Health Center Period January-April 2023 based on drug class and type of drug. This study is a descriptive study with a retrospective approach conducted in June 2023, in the patient visit book there were 60 patients with ARI from January to April 2023. Based on the age range where the age of >61 years and above the most suffer from ARI, namely 20 cases (33%) and at the age of 1-10 years as many as 18 cases (30%). Based on the drug class in the classification of the most widely used drugs, namely the vitamin group where there were 44 cases (73.33%). Based on the type of drug most widely used, namely Paracetamol where there were 35 cases (17.32%). Suggestion: For further research, it is hoped that ongoing research can be carried out with the category of evaluating the use of ARI drugs so that researchers can directly observe the patient's condition.